Simultaneous quantification of fourteen characteristic active compounds in Eucommia ulmoides Oliver and its tea product by ultra-high performance liquid chromatography coupled with triple quadrupole mass spectrometry (UPLC-QqQ-MS/MS). (30th September 2022) - Li, Xin-Yue; Fu, Yu-Jie; Fu, Yue-Feng; Wei, Wei; Xu, Cheng; Yuan, Xiao-Han; Gu, Cheng-Bo
Abstract: Various kinds of bioactive compounds contribute to versatile health-promoting properties of Eucommia ulmoides Oliver ( E. ulmoides ). In present study, we developed a UPLC-QqQ-MS/MS method for simultaneous quantification of fourteen characteristic active compounds, including 3 lignans, 4 iridoids, 3 flavonoids and 4 phenolics in E. ulmoides and its tea product for the first time. The running time of the method is 6.5 min. It has good linearity, sensitivity, precision, accuracy, and stability. Using this high-throughput method, the distributions of fourteen characteristic active compounds in E. ulmoides and its tea product were clarified. Also, it was found that E. ulmoides tea exhibited superiority in contents of chlorogenic acid as compared with natural resources. Overall, the study provided a rapid, reliable, and efficient analysis method, which could be applied for the quality evaluation of E. ulmoides natural resources and their relative products in the field of food and medicine.